Evolution of lacewings and allied orders using anchored phylogenomics (Neuroptera, Megaloptera, Raphidioptera). (23rd November 2017) - WINTERTON, SHAUN L.; LEMMON, ALAN R.; GILLUNG, JESSICA P.; GARZON, IVONNE J.; BADANO, DAVIDE; BAKKES, DEON K.; BREITKREUZ, LAURA C.V.; ENGEL, MICHAEL S.; LEMMON, EMILY MORIARTY; LIU, XINGYUE; MACHADO, RENATO J.P.; SKEVINGTON, JEFFREY H.; et al.
Abstract: Analysis of anchored hybrid enrichment (AHE) data under a variety of analytical parameters for a broadly representative sample of taxa (136 species representing all extant families) recovered a well‐resolved and strongly supported tree for the higher phylogeny of Neuropterida that is highly concordant with previous estimates based on DNA sequence data. Important conclusions include: Megaloptera is sister to Neuroptera; Coniopterygidae is sister to all other lacewings; Osmylidae, Nevrorthidae and Sisyridae are recovered as a monophyletic Osmyloidea, and Rhachiberothidae and Berothidae were recovered within a paraphyletic Mantispidae. Contrary to previous studies, Chrysopidae and Hemerobiidae were not recovered as sister families and morphological similarities between larvae of both families supporting this assumption are reinterpreted as symplesiomorphies. Relationships among myrmeleontoid families are similar to recent studies except Ithonidae are placed as sister to Nymphidae. Notably, Ascalaphidae render Myrmeleontidae paraphyletic, again calling into question the status of Ascalaphidae as a separate family. Using statistical binning of partitioned loci based on a branch‐length proxy, we found that the diversity of phylogenetic signal across partitions was minimal from the slowest to the fastest evolving loci and varied little over time. Ancestral character‐state reconstruction of the sclerotization of the gular region in the larval head found that although it is present in Coleoptera, Raphidioptera and Megaloptera, it is lost early in lacewing evolution and then regained twice as a nonhomologous gula‐like sclerite in distantly related clades. Reconstruction of the ancestral larval habitat also indicates that the ancestral neuropteridan larva was aquatic, regardless of the assumed condition (i.e., aquatic or terrestrial) of the outgroup (Coleopterida). Abstract : A phylogeny of Neuropterida is presented using anchored hybrid enrichment genomic data for 136 species across all families. Phylogenomic analysis supports Coniopterygidae as sister to the rest of the order, as well as paraphyly of Myrmeleontidae relative to Ascalaphidae. Ancestral character state reconstructions recover multiple origins for the gular-like sclerite in lacewing larvae, and that the ancestral lacewing had an aquatic larva.